2021
DOI: 10.3390/en14164899
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Performance Potential with a High-Temperature Phase Change Dispersion

Abstract: Phase change dispersions are useful for isothermal cooling applications. As a result of the phase changes that occur in PCDs, they are expected to have greater storage capacities than those of single-phase heat transfer fluids. However, for appropriate heat exchanger dimensions and geometries for use in phase change dispersions, knowledge about the convective heat transfer coefficients of phase change dispersions is necessary. A test unit for measuring the local heat transfer coefficients and Nusselt numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Differential scanning calorimetry (DSC) and T-history analyses showed that the apparent specific heat capacity of the sample doubled that of water at around 323 K [18]. The heat transfer performance of that same emulsion and its potential for advanced temperature management in high voltage electrical devices was experimentally and numerically evaluated in two recent works from the same authors [19,20]. When it comes to fatty alcohols such as 1-hexadecanol (also known as cetyl or palmityl alcohol), these materials have proved effective as core for the preparation of micro- [21][22][23][24][25] or nano-encapsulated [26] PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) and T-history analyses showed that the apparent specific heat capacity of the sample doubled that of water at around 323 K [18]. The heat transfer performance of that same emulsion and its potential for advanced temperature management in high voltage electrical devices was experimentally and numerically evaluated in two recent works from the same authors [19,20]. When it comes to fatty alcohols such as 1-hexadecanol (also known as cetyl or palmityl alcohol), these materials have proved effective as core for the preparation of micro- [21][22][23][24][25] or nano-encapsulated [26] PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 2-3 years, several nanoemulsions fulfilling the above-mentioned TES material requirements have been validated for use in different heat storage applications [47][48][49][50][51][52]. Additionally, several composite or hybrid materials have been studied and proposed as PCMs with improved thermo-physical properties [53][54][55][56].…”
Section: Nanoemulsions As Tes Fluids: Advantagesmentioning
confidence: 99%